A Sami analytical solution of non-Newtonian Maxwell hybrid nano-fluid over a stretching sheet with Cattaneo-Christov heat and mass flux model - Ayesha Bibi; Waris Khan; Ali Arishi; Imed Boukhris; Mohamed Kallel; Afnan Al Agha; Hakim AL Garalleh (Results in Engineering)
A non-Newtonian fluid is one whose viscosity changes with applied stress, meaning it does not obey Newton’s law of viscosity. Non-Newtonian and hybrid nanofluid flow analysis attracts great research attention due to its extensive applications in current fields and the advancement of technology. Therefore, the objective of this research is to present a semi-analytical solution of the non-Newtonian Maxwell hybrid nanofluid flow over a stretching sheet using mass flux and CattaneoChristov heat models. Alumina (Al₂O₃) and magnetite (Fe₃O₄) nanoparticles are combined to form a mixture of nanoparticles. The heat transmission rate for Maxwell hybrid nanofluid is controlled by considering Brownian motion, activation energy, thermophoresis, radiation, and magnetic effects. The partial differential equations with corresponding boundary constraints are transformed into a set of nonlinear ODEs using similarity transformations and some parameters. After formulating the model, a combination of the shooting method and MATLAB’s BVP4C solver is employed to solve the nonlinear ODEs and graphically illustrate the results. This study shows how the temperature and concentration profile are impacted by Brownian motion and the magnetic field's effect on velocity caused by the Lorentz force. Skin friction, heat, mass flux, magnetic factor, and Nusselt number were among the parameters that were examined and graphed to show their effects on temperature, concentration, and velocity fields.